Moral foundations and voluntary public good provision: The case of climate change - Heinz Welsch (University of Oldenburg, Department of Economics, 2019)
Economic theory has invoked moral motivation as an explanation for the voluntary provision of public goods but is vague with regard to the specific moral concerns involved. Using climate change as a case study, this paper relates morally-motivated public good provision to the six moral foundations (MFs) identified by moral psychologists: Care, Fairness and Liberty (individual-focused), and Loyalty, Authority and Sanctity (group-focused). Using data from the European Social Surveys it is found that using the MFs in addition to standard explanatory variables improves the explanation of climate-friendly behaviors and endorsement of climate-friendly regulations by 44 percent. While the Fairness and Care foundations are strong and robust predictors of the dependent variables, the Loyalty foundation contributes positively only when neglecting the nature of climate change mitigation as a global public good. More generally, in contrast to the individual-focused MFs (that apply to all individuals), the group-focused MFs are of little direct relevance for climate change mitigation, as the benefit from mitigation extends beyond the in-group (family, neighborhood, region, or nation) to which these MFs refer. Group-focused MFs are only of indirect relevance as their endorsement fosters general environmental concern.
Keywords: H41; H23; Q54; D91; 330; voluntary public good provision; climate change; moral motivation; moral foundations